Kuwait : Staff Report for 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
Kuwait's 2005 Article IV Consultation reports that the economic and financial positions are projected to remain strong mainly on the expectation that world oil prices will decline only gradually. Reflecting sharply higher oil prices and production, economic conditions improved significantly in 2003 and 2004. The main economic challenge facing Kuwait is to create sufficient employment opportunities for the rapidly growing national labor force by accelerating the growth of the private non-oil economy.